PENGARUH PENYULUHAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARA SENDIRI DI SMK NEGERI 3 RAMBAH - Hikmah, Nurul; Bewelli Fahmi, Yuyun (Jannatul Makwa Health : Jurnal Ilmiah Kesehatan (Scientific Journal of Health), 2026)
Globocan data from 2020 by the World Health Organization (WHO) shows that the number of new breast cancer cases reached 68,858 cases (16.6%) out of a total of 396,914 new cancer cases in Indonesia. One of the appropriate efforts in early detection of breast abnormalities, especially breast cancer, is by performing a breast self-examination. (SADARI). The purpose of this research is to determine the effect of health education on breast self-examination on the knowledge of female adolescents about Breast Self-Examination (SADARI) at SMK Negeri 3 Rambah. The type of research used is experimental research with a pretest-posttest group design approach, which involves conducting a pretest (initial observation), followed by providing counseling to a group, and then conducting a posttest (final observation) using total sampling technique with a sample size of 20 people by administering 20 questions through a questionnaire. Data analysis in this study used the Paired Sample T-Test statistical test. The results showed an influence of counseling on the knowledge of adolescent girls (p value = 0.000 <0.05). This study indicates that counseling has an effect on the knowledge of adolescent girls about breast self-examination (SADARI) at SMK Negeri 3 Rambah. Health counseling about SADARI needs to be continued with a larger number of respondents, especially adolescent girls, as an effort to increase their knowledge about SADARI to detect early signs of lumps or abnormalities in the breasts.